International dispute settlement - Merrills, J. G. (Cambridge, UK ; New York : Cambridge University Press, 2011)
"A guide to the techniques and institutions used to solve international disputes, how they work and when they are used. This textbook looks at diplomatic (negotiation, mediation, inquiry and conciliation) and legal methods (arbitration, judicial settlement). It uses many, often topical, examples of each method in practice to place the theory of how things should work in the context of real-life situations and to help the reader understand the strengths and weaknesses of different methods when they are used. It also looks at organisations such as the International Court and the United Nations and has been fully updated to include the most recent arbitrations, developments in the WTO and the International Tribunal for the Law of the Sea, as well as case law from the International Court of Justice"--Provided by publisher.
Machine generated contents note: 1. Negotiation; 2. Mediation; 3. Inquiry; 4. Conciliation; 5. Arbitration; 6. The International Court I: organisation and procedure; 7. The International Court II: the work of the Court; 8. The Law of the Sea Convention; 9. International trade disputes; 10. The United Nations; 11. Regional organisations; 12. Trends and prospects; Appendix A. Agreement between Argentina and the United Kingdom establishing an Interim Reciprocal Information and Consultation System, 1990; Appendix B. Report of the Commission of Inquiry into the Red Crusader Incident, 1962 (extract); Appendix C. Conciliation Commission on the Continental Shelf Area between Iceland and Jan Mayen, May 1981; Appendix D. Arbitration Agreement between the United Kingdom and France, July 1975; Appendix E. Special Agreement for Submission to the International Court of Justice of the Differences Between the Republic of Hungary and the Slovak Republic Concerning the Gabcikovo-Nagymaros Project (1993); Appendix F. Optional Clause Declarations (Peru, Djibouti, Japan, Germany); Appendix G. WTO: Rules of Conduct for the Understanding on Rules and Procedures Governing the Settlement of Disputes (extract); Appendix H. Security Council Resolution 915, establishing UNASOG, May 1994; Appendix I. Terms of Reference of the Trust Fund for the International Tribunal for the Law of the Sea (2000); Appendix J. Ruling Pertaining to the Differences between France and New Zealand Arising from the Rainbow Warrior Affair (extract); Appendix K. CIS: Concept for Prevention and Settlement of Conflicts in the Territory of States members of the Commonwealth of Independent States (1996).
Includes bibliographical references and index.
Keywords: Pacific settlement of international disputes